From Conception to Childhood: The Evolution and Significance of Children's Human Rights - Dedisyah Putra; Kasman Kasman; Sumper Mulia Harahap; Amrar Mahfuzh Faza; Liantha Adam Nasution; Lazuardi Maulana Affan (Khazanah Hukum, 2025)
This study aims to examine the evolution and significance of children's human rights from conception to childhood, with a particular focus on the Indonesian context, which is rich in cultural and religious diversity. Through a qualitative approach with normative and historical methods, this study analyzes the development of international and national legal norms governing child protection, as well as how social and religious dynamics influence the understanding of children's rights, especially in the prenatal phase. Data were collected through a documentary study of international legal instruments such as the Convention on the Rights of the Child (CRC), Indonesian laws and regulations, as well as academic literature and reports from international organizations. The results of the study show that although Indonesia has adopted various instruments for protecting children's rights, there are still normative gaps related to the recognition and protection of children's rights from infancy. Differences in views arising from cultural and religious diversity are both challenges and potential in formulating more inclusive policies. Therefore, a legal approach is needed that is not only based on international standards but is also sensitive to local values. This study is expected to contribute to the development of more comprehensive and contextual child protection policies in Indonesia.